PERAN MOTIVASI INTRINSIK SEBAGAI PEMEDIASI ANTARA KEPRIBADIAN PROAKTIF DAN KREATIVITAS - Asri Sekar Mawar Firdausi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
The development of the tourism sector in Indonesia resulted in the growth of accommodation providers, both in the form of hotels and non-hotels. The number of accommodation providers has resulted in increasingly intense competition in the industry. Departing from these problems, workers in the industry need to have creative skills in order to be able to compete. Therefore, this study analyzes the effect of a proactive personality on creativity with intrinsic motivation as a mediator. This study uses 3-star hotel employees in Yogyakarta, as many as 168 respondents as a sample. Data analysis was performed using CB-SEM with the help of AMOS software. Based on the data testing results, it was found that proactive personality and intrinsic motivation positively influence creativity. Meanwhile, intrinsic motivation is proven not to mediate the influence of a proactive personality on creativity. Based on these findings, organizations need to be able to select employees who have a proactive personality and provide encouragement from within for their workers so that creativity can be optimally created.